ANOTHER LOOK AT THE 1957 STATEMENT. - Vatter, William J. (The Accounting Review, 1962)
The article focuses on the Accounting and Reporting Standards for Corporate Financial Statements, 1957 Revision." The ideal statement of concepts and standards for published financial reports must represent some degree of compromise and generality. It cannot be expected to justify or condemn every procedure that might be adopted, nor to promote absolute uniformity. But it must provide a basis for judging issues that do in fact exist or that might reasonably arise in the preparation of financial statements. These issues do not remain fixed over time, nor do the methods of dealing with them stay settled. The 1957 statement-however acceptable for its time and situation-must be viewed as subject to revision and restatement; as subsequent events have broadened the area of discussion, revealed new problems, and changed attitudes and conclusions about some of the old ones. When one compares the 1957 statement with its predecessors, it is clear that one has come a long way. Yet, perhaps because of that progress, one may see clearly still more that could and should be done.